Perceived Legitimacy of CVE Policies and the Willingness to Report Concerns of Radicalization to Authorities in the Nordic Countries - Gøtzsche-Astrup, Oluf (Terrorism and political violence, 2023)
Approaches to countering violent extremism (CVE) increasingly call upon ordinary citizens to report concerns regarding radicalization to authorities. However, knowledge about the factors determining their willingness to report remains limited. This paper addresses this void by asking under what circumstances members of the public are willing to report concerns of radicalization to authorities. The paper reports findings from a large-scale, comparative survey experiment fielded to nationally representative samples in Sweden, Denmark, Norway and Finland (n = 7,389) as well as eight city representative samples (two in each country, n = 6,603). We investigate how perceptions of the appropriateness, inclusiveness, implementation and outcome of CVE policies combine in forming perceptions of the legitimacy of CVE policy, and how manipulations of perceived legitimacy shape willingness to collaborate with authorities. Both cross-country and cross-city differences in willingness to report concerns of radicalization are explored. The results show that the more legitimate citizens perceive CVE policies to be, the more willing they are to contact authorities to report concerns of radicalization, while perceptions of CVE policies as illegitimate lead to a preference for reactions involving “intimates” of the individual in question and short of reporting to authorities. The implications of the findings for CVE practices are discussed.